Determination of natural carotenoid pigments from freshwater green algae as potential halal food colorants - Othman, Rashidi; Noh, Nur Hidayah; Ahmad Fadzillah, Nurrulhidayah; H., Anis Hamizah; Jamaludin, Mohd Aizat (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
It is noted that nowadays, halal products are gaining wider recognition as a new benchmark for safety and quality assurance. As a consequence of these additional pigment needs, the demand in isolated natural colorants has increased as compared with synthetic dyes. The aim of the research is to explore new sources of pigments to be used as halal food colorants. This quest is not only directed in finding natural alternatives for synthetic dyes, but also with the aim to discover new taxons for the pigment production, for instance from microalgae. Therefore, a total of six freshwater algae species were evaluated quantitative and qualitatively using HPLC for carotenoids pigment. Three main carotenoids were identified in Chlorella fusca, Chlorella vulgaris, Selenastrum capricornutum, Pandorina morum, Botryococcus sudeticus and Chlorococcum sp. which are lutein, β-cryptoxanthin and β-carotene. The ratio of these carotenoids varies between species where lutein was detected substantially higher in Chlorella fusca (69.54±11.29µg/g DW); β-cryptoxanthin in Pandorina morum (1.24±0.33 µg/g DW) whereas β-carotene in Chlorella vulgaris (18.42±9.2 ug/g DW). The significant outcome of the research will be new findings of new natural carotenoid pigment sources as potential food colorants and bioactive compounds which can be beneficial to halal health promoting products industry, food products and dye technology which covers not only the Shariah requirement, but also the hygiene, purification and safety aspects.